Genetic divergence in maize regarding grain yield and tassel traits (Revista Ciência Agronômica, 2021)
Maize tassels with a longer length and higher number of branches prevent the passage of solar radiation into theupper plant canopy and act as a drain for photoassimilates that could be used for grain production. This study aimed to verify if thereis genetic divergence regarding grain yield and tassel traits among maize cultivars in three agricultural years. Twenty maize cultivarswere evaluated and 11 tassel traits and grain yield were measured. Individual and joint analyses of variance were performed for eachtrait. Principal component analysis was performed, the generalized Mahalanobis distance matrix between cultivars was determined,and the genetic divergence analysis was performed, using the unweighted pair group method with arithmetic mean (UPGMA),which allowed constructing the dendrogram. The cophenetic correlation coeffi cient was calculated to validate the cluster. There isgenetic divergence among maize cultivars and six groups of cultivars were formed. Tassel length, total branches number, centralspike dry matter, and grain yield are the traits that most contribute to the genetic divergence among maize cultivars.